Societal acceptance increases Muslim-Gay identity integration for highly religious individuals… but only when the ingroup status is stable. Issue 3 (3rd April 2022) - Koc, Yasin; Sahin, Helin; Garner, Alex; Anderson, Joel R.
ABSTRACT: Reconciling religious beliefs with a sexual minority identity can be challenging. After coming out, many gay men report to renounce their religious identity or experience increased identity conflict between their religious and sexual identities. Giving up one's own identity or identity conflict are known to predict negative wellbeing, and it is important to find ways to reduce this conflict and increase identity integration. In this experiment, we conceptualized identity integration as a social creativity strategy, and we examined whether societal acceptance (vs rejection) and ingroup experience (e.g., whether gay community feels stability or improvement about their status) would alter one's level of Muslim-gay identity integration. We found that Muslim-gay identity integration was highest among highly religious gay men when societal acceptance was present and ingroup experience was stable. Overall, we discuss our findings by drawing parallels between social identity theory and bicultural identity integration framework, and provide implications to increase identity integration for those with multiple conflicting identities.